The non-conformance of in-transit citrus container shipments to cold protocol markets: A systematic literature review. (July 2021) - Khumalo, Gculisile; Goedhals-Gerber, Leila L.; Cronje, Paul; Berry, Tarl
Abstract: The cold chain is vital in the reduction of physiological developments in citrus fruit to prolong the shelf-life and influence market rates. It is also important for some niche export markets that have specified time-temperature cold treatment protocols as phytosanitary risk mitigation measures for pests that they deem to be of phytosanitary concern. The review covers 44 publications that relate to the non-conformance of in-transit citrus shipments with cold-chain specifications. The findings indicate that the literature can be categorised into different themes, namely technological trends, temperature control, and cold-chain modelling and refrigeration. In addition, the key findings from the literature reviewed show that most non-conformances that occur are due to temperature deviations in the cold chain. In addition, the study suggests a framework for successful engagement with the cold-treatment process. The framework adapted from a citrus industry assessment conducted in 2016 provides a detailed explanation of the different phases and processes that need to be followed to help minimise the occurrence of non-conformances, while also detailing some of the disadvantages of the three components that the framework is comprised of. The three components are: the pre-cooling phase, the container-packing phase and the pulp/probe-stabilisation phase. The results of the study serve as a basis to further develop the research area by presenting recommendations and proposing future research. Highlights: The cold chain is key to the reduction of issues in citrus to prolong the shelf-life. The review covers 44 publications linked to the non-conformance of citrus shipments. The findings indicate that the literature can be categorised into different themes. The study suggests a framework for success in the cold-treatment process. The results of the study present recommendations and propose future research.